Interspecific and intraspecific analysis of Selinum spp. collected from Indian Himalayas using DNA barcoding - Ravi Prakash Srivastava; Gauri Saxena; Lav Singh; Arpit Singh; Praveen C. Verma; Gurminder Kaur (Journal of Genetic Engineering and Biotechnology, 2022)
Abstract Background DNA barcoding is a powerful method for phylogenetic mapping and species identification. However, recent research has come to a consistent conclusion about the universality of DNA barcoding. We used matK and rbcL markers to test the universality of twelve accessions from different locations belonging to two Selinum species, Selinum tenuifolium Wall. C. B. Clarke and Selinum vaginatum C. B. Clarke, keeping in mind their ability to identify species and establish phylogenetic relationships within and between the accessions. Results The success rates of PCR amplification using matK and rbcL were 75.26% ± 3.65% and 57.24% ± 4.42%, and the rate of DNA sequencing was 63.84% ± 4.32% and 50.82% ± 4.36%, respectively, suggesting that success rates of species identification of the two fragments were higher than 41.00% (matK, 41.50% ± 2.81%; rbcL, 42.88% ± 2.59%), proving that these fragments might be used to identify species. The best evolutionary tree with good supporting values was produced utilizing combinations of matK + rbcL markers when phylogenetic relationships were built with random fragment combinations. The twelve accessions of Selinum collected from different locations and their molecular sequences of matK and rbcL markers were blasted with other genera of Apiaceae family, and it was found that Selinum is most closely related to Angelica species of Apiaceae family. Conclusion The present study has grouped twelve accessions of Selinum species using molecular markers into phylogenies, which is first-of-its-kind report that established interrelationships within different species of Apiaceae with respect to Selinum. Graphical abstract